Study on the Safety and Security of Dangerous Goods at Compagnie Africaine d'Aviation: Kinshasa Stopover in the Democratic Republic of Congo - Ngbangu Woza Eric; Molongo Mokondande Médard; Ngalakpa Ziada Héritier; Nzolowa Banze Françis; Muhammad Ridwan (Budapest International Research and Critics University, 2023)
The aim of this study is to examine the correct handling of dangerous goods by Compagnie Africaine d'Aviation (CAA), in order to limit the risks that could arise from non-compliance with the rules governing the safety and security of dangerous goods. A mixed-methods approach was adopted, using descriptive, analytical and comparative methods, as well as interview, survey, observation and documentation techniques. Data collection and analysis showed that air transport of hazardous materials or products by Compagnie Africaine d'Aviation, despite the existence of regulatory standards, does not really comply with the minimum provisions set by the International Civil Aviation Organization and the Civil Aviation Authority of the Democratic Republic of Congo in terms of safety and security. A low level of handling of dangerous goods was observed in first position with 60%, followed by a medium level of 30% and a very low level of 10%. In view of this result, it should be pointed out that resources need to be invested in training and capacity building for personnel handling these dangerous products.